Effect of total replacement of inorganic with organic sources of key trace minerals on performance and health of high producing dairy cows - P.H. Pomport; H.E. Warren; J. Taylor-Pickard (Journal of Applied Animal Nutrition)
The aim of this trial was to compare the effect of complete replacement of certain inorganic trace minerals with organic, chelated minerals (Bioplex®, Selplex®; Alltech Inc, USA) against standard and reduced inorganic mineral levels in feed on the performance and health of dairy cows during a 10-week trial (W0-W10) period. Three treatment groups, each containing 36 dairy cows, were assigned to one of three diets that varied only in mineral feed composition: (1) Inorganic (CON) Cu (1,042 mg/kg), Se (26 mg/kg) and Zn (4,200 mg/kg) as per normal industry inclusion levels; (2) Inorganic (INORG) Cu (-35%: 680 mg/kg), Se (-60%; 10 mg/kg) and Zn (-66%; 1,360 mg/kg) (based on the lower organic levels in diet 3); and (3) Organic (proteinates and selenium-enriched yeast) minerals (ORG) Cu, Se and Zn as per INORG levels. The cows in the ORG group had the highest milk yield (32.6 kg; P=0.0165) with the INORG group the least (31.3 kg), production (energy corrected milk 31.5 kg (P=0.008) vs CON 31.0 kg and INORG 30.7 kg), protein synthesis (ORG 1,024 g/d (P<0.0001) vs CON 1,013 g/d and INORG 982 g/d) and ORG had the highest (P<0.01) milk lactose content. There were no differences between treatments in plasma Zn, Cu and GSH-PXE levels. Pregnancy rate and number of artificial insemination services appeared improved. Mastitis rates were lowest for the ORG group (two cows affected), vs four cows for the INORG group and six cows for the CON group. Somatic cell counts were consistently lower in the ORG cows (P<0.05), being less than 300,000 cell counts, compared to peaks of 380,000 counts in the INORG and 550,000 counts in the CON groups. Five cows were affected by lameness in the INORG group, compared to three for the CON and one in the ORG groups.